THE ROLE OF RESOURCE EFFICIENCY IN MODERATING THE INFLUENCE OF FIRM FUNDAMENTALS ON DIVIDEND POLICY - Hidayat, Riskin; Rosita, Rosita; Susanto, Heri (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
This research aims to examine the role of resource efficiency as a measure of the activity ratio in moderating the influence of firm fundamentals as measured by profitability and debt policy. Resource efficiency in this research is grouped into two, namely efficient and inefficient companies. The population of this research are companies incorporated in the Kompas 100 Index listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling, with the criteria that companies indexed by Kompas 100 during the period 2018-2022 consistently and pay dividends. Based on the sampling results, there are 42 companies that meet the criteria, so the number of observations in this research is 210.The data analysis technique uses moderation regression. The results showed that profitability has a significant positive influence on dividend policy, but debt policy has a negative and insignificant influence on dividend policy. Resource efficiency proxied by 1-TATO is able to moderate the influence of profitability and debt policy with dividend policy. From the results of this research, it means that resource efficiency has an important role for companies in determining the firm's dividend policy.